Optimizing Prehospital Stroke Care: A Comprehensive Literature Review - Al Sawidan, Saleh Ali M; Alsalah, Ali Jaber M; Alsalah, Bakkar Jaber Marshad; Abosaaq, Abdulaziz Jaber; Alalhareth, Nasser Dhafer; Al Swidan, Abdullah Musleh Mohammed; Alyami, Hamad Ali Hamad; Al Mansour , Ali Saleh Mana; Aldosari, Abdullah A . S; Almas, Yousef Hadi Saleh (Journal of Ecohumanism, 2024)
Prehospital stroke care plays a pivotal role in improving patient outcomes by facilitating rapid identification, triage, and transport to appropriate medical facilities. This literature review examines recent advancements and persistent challenges in optimizing prehospital stroke management. Key areas of focus include the effectiveness of stroke recognition tools such as FAST, the implementation of standardized EMS protocols, and the integration of telemedicine and mobile stroke units to enhance real-time decision-making. The review also highlights disparities in prehospital care delivery, particularly between urban and rural settings, and explores emerging trends like artificial intelligence and biomarker diagnostics. While significant progress has been made, barriers such as training inconsistencies, technology adoption challenges, and delayed EMS response times continue to impede optimal outcomes. This study underscores the importance of developing unified protocols, leveraging innovative technologies, and addressing regional disparities to strengthen the stroke chain of survival. Future research directions emphasize the need for longitudinal studies and enhanced collaboration between EMS systems and stroke centers to ensure equitable, efficient, and effective prehospital care.